Answer:
23
Step-by-step explanation:
I'm going to start by solving the first equation like so,
y - 8 = 15 (Remember what we do to one side we MUST do to the other)
<u> +8 +8 </u>
y = 23
So know we know y = 23 What we have to do now is replace 23 for y in the second equation.
y - 0 = ?
23 - 0 = 23
Hope that helps and have a great day!
D is the answer 6660
mark me brainiest if i right ty
Answer:
(- 3, - 6 ) , (1, 2 )
Step-by-step explanation:
2y = 4x ( divide both sides by 2 )
y = 2x → (1)
x² + y = 3 → (2)
Substitute y = 2x into (2)
x² + 2x = 3 ( subtract 3 from both sides )
x² + 2x - 3 = 0 ← in standard form
(x + 3)(x - 1) = 0 ← in factored form
Equate each factor to zero and solve for x
x + 3 = 0 ⇒ x = - 3
x - 1 = 0 ⇒ x = 1
Substitute theses values into (2) for corresponding values of y
x = - 3 : y = 2(- 3) = - 6 ⇒ (- 3, - 6 )
x = 1 : y = 2(1) = 2 ⇒ (1, 2 )
He has a total of $58.19.
1 day = $2.74
58.19/2.74
21.24
You can't have 21.2 days, so you need to round down to 21.
Jim can buy lunch for 21 days before he runs out of money on his account.
Don’t listen to the people who give you the links